1998
DOI: 10.1073/pnas.95.12.7018
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-binding growth factors: Production and characterization of functional fusion proteins having a collagen-binding domain

Abstract: The autocrine͞paracrine peptide signaling molecules such as growth factors have many promising biologic activities for clinical applications. However, one cannot expect specific therapeutic effects of the factors administered by ordinary drug delivery systems as they have limited target specificity and short half-lives in vivo. To overcome the difficulties in using growth factors as therapeutic agents, we have produced fusion proteins consisting of growth factor moieties and a collagen-binding domain (CBD) der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 17 publications
1
112
0
Order By: Relevance
“…8B). Positive binding of the mutated enzyme to G(POG) 8 peptide was also observed by surface plasmon resonance. In this binding profile (Fig.…”
Section: Binding Of the Recombinant Colg To The Peptide Substrate-mentioning
confidence: 94%
See 3 more Smart Citations
“…8B). Positive binding of the mutated enzyme to G(POG) 8 peptide was also observed by surface plasmon resonance. In this binding profile (Fig.…”
Section: Binding Of the Recombinant Colg To The Peptide Substrate-mentioning
confidence: 94%
“…6B). The proteins did not bind to Sepharose beads coupled with any of the following 24-mer peptides; (PG) 12 , (PPPG) 6 , all-D-(PPG) 8 , (APG) 8 , or (PAG) 8 (Fig. 6C, lanes 1-5) or to gelatin-Sepharose beads (Fig.…”
Section: Purification Of the C-terminalmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical interactions, such as hydrogen bonding, hydrophobic, and ionic interactions and biological affinity interactions, provide a much more convenient and natural way of conjugating agents to proteins and other macromolecules as opposed to covalent chemical attachment. 21 For example, biotin-avidin interactions, metal-mediated histidine-NTA interactions, and antigen-antibody binding are all effective protein conjugation tools in biology research. Recent studies on collagens have shown that even at physiological conditions, type I collagen is thermally unstable.…”
Section: Introductionmentioning
confidence: 99%